Breastfeeding Practices in Infants in the West Region of Cameroon - A Chiabi; BG Kamga; E Mah; S Nguefack; P Fokam; W Tafen; PF Tchokoteu (Tehran University of Medical Sciences, 2011)
Background: The study was conducted to evaluate the knowledge, attitudes and practices of breast-feeding in the West region of Cameroon. Methods: A cross sectional descriptive study was conducted in two health facilities on 195 mother-infant pairs, seen at the out patient and vaccination units of the Bafoussam Regional Hospital over a period of one month from 1st to 30th September 2008. The socio-demographic characteristics of mothers, knowledge on breastfeeding and the practice of breastfeeding were studied. Data was analyzed using the SPSS software. The chi square and student t- test were used for comparison and results considered significant for P< 0.05. Results: Breastfeeding was practised by 99.48% of the mothers. Only 33.8% of the mothers knew that they had to exclusively breastfeed up to 6 months, and 20% effectively breastfed up to 6 months. The mean duration of breastfeeding was 5.06 months and negatively correlated with the number of children and the profession of the mother. In 69.74% of the women, nothing was given to the baby before the first breastfeed. Discontinuation of breastfeeding was done averagely around 15.24 months and earlier in married women and in those with a higher educational level. Conclusion: Although the majority of parents practised breast feeding, only a minority understood its benefits, so more should be done to educate the community on the benefits of exclusive breast-feeding for up to six months.